Sociodemographic profile of the people living with elimination stoma in a Stomatherapy Service at a University Hospital in Southern Brazil (Research, Society and Development, 2022)
To analyze the epidemiological profile of people with stomas treated at the Stomatherapy Service of a University Hospital in southern Brazil. Method: a quantitative, retrospective study of patients registered at the service since its creation 30 years ago. Data were collected in August and September 2022 from the registration forms of 150 patients treated in the sector. These were exported and organized into a table in Microsoft® Excel software and analyzed by the R Commander software program. Results: It was found that 51.3% (77) are men; As for age, 56.7% (85) are over 60 years old; 40% (60) have incomplete elementary education; 92.7% (139) of the stomas are of pathological etiology, with 36% (50) rectal cancer being the most prevalent. As for the type of ostomy, 68.7% (103) have a colostomy. As for race/ethnicity, 84% (126) declared themselves white. As for marital status, 44% (66) are married. As for the place of residence, 96.7% (145) live in the urban area. As for the time of permanence of the stoma, 61.3% (92) have temporary stomas; 53.3% (80) are linked to the Service between one and seven years. Conclusion: The identification of the profile of people assisted in the Stomatherapy Service makes it possible to organize the assistance, developing unique therapeutic plans in order to meet their individual needs.